The Pedagogical Content Knowledge and Occupational Socialization in Preservice Physical Education Teachers - Dong Zhang; Zhenyu Shi; Yafei Cheng (SAGE Open)
The goal of this study was to predict the preservice physical education teachers’ (PPETs) occupational socialization (OS) by their pedagogical content knowledge (PCK) and to investigate the relationship between them. The participants were 56 PPETs from a physical education teacher education (PETE) undergraduate program in the northeastern United States. This research work utilized the mixed-methods research design. An online survey with the PCK standard test, the teachers’ occupational beliefs survey, and a semistructured interview were used to collect data. The PPETs’ PCK significantly predicted their OS. More PCK would lead to more positive and professional OS development. Furthermore, the methods classes were the most important resource to learn PCK and develop the OS of the PPETs. There is a close and direct relationship between PPETs’ PCK and OS, and early field experience (EFE) is a common carrier. It is possible to use PPETs’ PCK to infer their OS development, and quantitative methods are effective for examining both factors. PETE programs should purposefully set up EFEs to improve PPETs’ PCK and OS simultaneously.